Impact of Gastrostomy Placement on Nutritional Status, Physical Health, and Parental Well-Being of Females with Rett Syndrome: A Longitudinal Study of an Australian Population - Wong, K.; Downs, Jennepher; Ellaway, C.; Baikie, G.; Ravikumara, M.; Jacoby, P.; Christodoulou, J.; Elliott, E.J.; Leonard, H. (MOSBY-ELSEVIER, 2018)
© 2018 Elsevier Inc.